Antinociceptive and Antipruritic Effects of HSK21542, a Peripherally-Restricted Kappa Opioid Receptor Agonist, in Animal Models of Pain and Itch - Wang, Xin; Gou, Xiaoli; Yu, Xiaojuan; Bai, Dongdong; Tan, Bowei; Cao, Pingfeng; Qian, Meilin; Zheng, Xiaoxiao; Wang, Hairong; Tang, Pingming; Zhang, Chen; Ye, Fei; et al. (Frontiers in Pharmacology, 2021)
Kappa opioid receptor (KOR) agonists have been promising therapeutic candidates, owing to their potential for relieving pain and treating intractable pruritus. Although lacking morphine-like central nervous system (CNS) effects, KOR agonists do elicit sedation, dysphoria and diuresis which seriously impede their development. Peripherally-restricted KOR agonists have a poor ability to penetrate into the CNS system, so that CNS-related adverse effects can be ameliorated or even abolished. However, the only approved peripherally-restricted KOR agonist CR845 remains some frequent CNS adverse events. In the present study, we aim to address pharmacological profiles of HSK21542, with an expectation to provide a safe and effective alternative for patients who are suffering from pain and pruritus. The in vitro experimental results showed that HSK21542 was a selective and potent KOR agonist with higher potency than CR845, and had a brain/plasma concentration ratio of 0.001, indicating its peripheral selectivity. In animal models of pain, HSK21542 significantly inhibited acetic acid-, hindpaw incision- or chronic constriction injury-induced pain-related behaviors, and the efficacy was comparable to CR845 at 15 min post-dosing. HSK21542 had a long-lasting analgesic potency with a median effective dose of 1.48 mg/kg at 24 h post-drug in writhing test. Meanwhile, the antinociceptive activity of HSK21542 was effectively reversed by a KOR antagonist nor-binaltorphimine. In addition, HSK21542 had powerful antipruritic activities in compound 48/80-induced itch model. On the other hand, HSK21542 had a weak ability to produce central antinociceptive effects in a hot-plate test and fewer effects on the locomotor activity of mice. HSK21542 didn’t affect the respiratory rate of mice. Therefore, HSK21542 might be a safe and effective KOR agonist and promising candidate for treating pain and pruritus.